Days of Antibiotic Spectrum Coverage (DASC) as a Metric for Evaluating the Impact of Prospective Audit and Feedback (PAF) against Long-Term Broad-Spectrum Antibiotic Use - Yuichi Shibata; Jun Hirai; Nobuaki Mori; Nobuhiro Asai; Mao Hagihara; Hiroshige Mikamo (MDPI AG, 2024)
The present study aimed to evaluate the impact of prospective audit and feedback (PAF) on the use of inpatient broad-spectrum antibiotics for more than 10 days using days of therapy (DOT) and a novel metric called days of antibiotic spectrum coverage (DASC) to assess whether the antimicrobial spectrum was narrowed. Conducted at Aichi Medical University Hospital in Japan, the study compared a six-month baseline period (April to September 2022) with a six-month intervention period (April to September 2023). The primary outcome measures were changes in DOT/patient and DASC/patient for broad-spectrum antibiotics. Propensity score matching was performed between two periods and a total of 172 patients were included in the study (pre-intervention, n = 86; intervention, n = 86). The DASC/patient of broad-spectrum antibiotics was statistically decreased in the intervention period compared to that in the baseline period (153.3 vs. 122.7, p < 0.05). Additionally, our PAF intervention led to a switch to narrow-spectrum antimicrobial therapy without increasing all-cause 30-day mortality (5.8% vs. 5.8%, p = 1.0). However, the DOT/patient, DASC/patient, and DASC/DOT of all antimicrobials were not significantly changed. Our study concluded that we should reconsider the timing of PAF intervention by evaluating the effort of PAF by using DOT and DASC.